(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The contemporary world’s interconnection might call into question long-held ideas of national or regional history. Global viewpoints and transnational narratives may arise, emphasising the linked nature of historical events and the significance of interpreting history from different perspectives, which might characterise historical destabilisation. Alice Borchardt’s views on feminism serve as the foundation for the historical conflict that takes place within its pages. It is worth noting that this contest is directly related to the novel’s topic. As a result of reading the work, one is reminded of history as the inheritor of man’s old vices, as being midway between monsters and people, and sometimes sharing the nature of both. Thus, in addressing history, Alice Borchardt exploits the feminine subject to destabilise it. One must accept that Alice Borchardt’s analytical discourse develops a feminine awareness set against the backdrop of historical configurations. While discussing history, she manipulates gender to express a new reality. This new reality is the constructed new subject, inexorably tied with humanism.